Concepts, skills of planning and implementing behaviour change communication activities (Nhà xuất bản [Hà Nội], 2007)
This book include concepts, terimnologies and basic skills of behaviour change communication; a guide to behaviour change communication in the reproductive health initiative for adolescents.